2017
DOI: 10.1080/00949655.2017.1341886
|View full text |Cite
|
Sign up to set email alerts
|

Fitting logistic multilevel models with crossed random effects via Bayesian Integrated Nested Laplace Approximations: a simulation study

Abstract: Fitting cross-classified multilevel models with binary response is challenging. In this setting a promising method is Bayesian inference through Integrated Nested Laplace Approximations (INLA), which performs well in several latent variable models. Therefore we devise a systematic simulation study to assess the performance of INLA with cross-classified logistic data under different scenarios defined by the magnitude of the random effects variances, the number of observations, the number of clusters, and the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
4
0
2
Order By: Relevance
“…As Bayesian statistics using Markov chain Monte Carlo (MCMC) can be computationally intensive and difficult to parametrize, a method using INLA to approximate the posterior marginal distribution and developed for R was used in our study [ 51 , 53 ]. Studies comparing R-INLA to other regression modeling methods have shown that R-INLA can be simpler to use and quicker in computation whilst yielding similar estimates to other Bayesian or generalized linear approaches [ 55 , 62 ]. We believe this was the most cost-effective approach in this particular study.…”
Section: Discussionmentioning
confidence: 99%
“…As Bayesian statistics using Markov chain Monte Carlo (MCMC) can be computationally intensive and difficult to parametrize, a method using INLA to approximate the posterior marginal distribution and developed for R was used in our study [ 51 , 53 ]. Studies comparing R-INLA to other regression modeling methods have shown that R-INLA can be simpler to use and quicker in computation whilst yielding similar estimates to other Bayesian or generalized linear approaches [ 55 , 62 ]. We believe this was the most cost-effective approach in this particular study.…”
Section: Discussionmentioning
confidence: 99%
“…The R-INLA inbuilt standard priors are the nature of R-INLA packages of INLA function. Different researchers [13][14][15] briefly used it. According to the study [7] by default, a flat improper prior for the intercept assumed in INLA and all other components of parameters assumed independent Gaussian with mean zero Normal (0,σ 2 ) with fixed precision σ −2 = 0.0001 a priori.…”
Section: Prior Distributions Of Parametersmentioning
confidence: 99%
“…In addition, the marginal posterior distribution for each element of hyper-parameter vector: Different researchers [11][12][13] briefly used it. According to the study [14] by default, a flat improper prior for the intercept assumed in INLA and all other components of parameters assumed independent Gaussian with mean zero Normal (0,𝜎 2 ) with fixed precision 𝜎 −2 = 0.0001 a priori.…”
Section: Integrated Nested Laplace Approximation (Inla)mentioning
confidence: 99%